PENGARUH PEMBERIAN BUNGKIL INTI KELAPA SAWIT YANG DIFERMENTASI MENGGUNAKAN ISOLAT SELULOLITIK DARI BELALANG KEMBARA PADA PAKAN TERHADAP PENAMPILAN PRODUKSI PUYUH JANTAN - Arif Pranata (Buletin Peternakan, 2015)
This research was conducted to examine the effects of fresh and fermented palm kernel cake (BIKS) supplementation in the diets on male japanese quail performance. Two hundred and ten day-old quails were randomly devided into seven treatment diets in three replications of ten quails each. The dietary treatments were: diet without palm kernel cake (control; K), control diets supplemented with 10%, 20% , 30% BIKS (BIKS10%, BIKS20%, BIKS 30%), control diets supplemented with 10%, 20%, 30% fermented palm kernel cake (BIKSF10%, BIKSF20%, BIKSF30%). The collected data were final body weight, feed consumption, feed conversion, and carcass production. Data were statistically analyzed by ANOVA, followed by Duncan’s New Multiple Range Test for any result with significant different. The results showed that dietary supplementation did not influence the final body weight and carcass production. The final body weight of the birds were 123.55, 122.34, 118.35, 122.24, 119.24, 124.72 and 121.95 g/head/35 day, carcass percentation were 65.35, 64.68, 64.87, 65.20, 66.57, 65.36, and 64.87%. However, Japanese quails that given fermented palm kernel cake had higher feed consumption and conversion ratio, except for the birds with 10% BIKSF. It might be concluded that the additions of BIKSF in diet did not give beneficial effects on the performance of Japanese quail.(Key words: Fermentation, Palm kernel cake, Performance, Quail)